An electromagnetic modulator based on electrically controllable meta-molecule analogue to spontaneous emission cancellation - Gao, Lei; Jiang, Zhuofan; Chen, Yongqiang; Fang, Yu; Wu, Xingzhi; Ding, Yaqiong; Sun, Yong (Frontiers in Physics, 2023)
In this article, we present a miniaturized electromagnetic modulator based on electrically controllable spontaneous-emission-cancellation-like (SEC-like) effect in meta-molecule. The SEC-like meta-molecule with in-unit destructive interference interaction is constructed by two detuned side-coupled resonators based on zero-index-metamaterial (ZIM). The subwavelength ZIM-based resonators, regarding as meta-atoms, are arranged symmetrically in a cut microstrip. A diode serving as an adjustable resistor is embedded in the gap of microstrip to inductively tune the interference of two ZIM-based meta-atoms. Numerical simulations indicate that the remarkable modulation on the SEC-like spectrum can be realized by changing the resistance from 9000 Ω (unconnected) to 10 Ω (connected). Microwave experiments validate the electromagnetic modulation in three narrow bands on the SEC-like spectrum, and a peak modulation contrast of 52.1 dB on the transmission at 2.59 GHz is achieved through electric biasing. The results in this work may pave the way for our design to be applied in new integrated active devices and applications.